(untitled) (Práxis Educativa, 2024)
There is a consensus that the appreciation of the teaching profession has a direct impact on improving the quality of teaching and public education. Thus, the aim of this article was to evaluate the implementation of teacher appreciation policies by Brazilian educational networks and systems, specifically those related to entry into the teaching profession, salary floor, and career plans. These three elements make up what is known as the constitutional tripod of teacher appreciation, but it has increasingly turned into a tripod of precarization. The study, of a qualitative approach, carried out a survey and analysis of official Basic Education data published by the National Institute for Educational Studies and Research Anísio Teixeira (INEP), specifically the Statistical Synopses of Basic Education and the Report of the 4th Cycle of Monitoring the Goals of the National Education Plan (2014-2024). The results highlight advances in teacher appreciation policies, but they still face obstacles to effective implementation. Keywords: Entry into the teaching profession. Salary floor. Career plans.